PERBANDINGAN MANAJEMEN PELAYANAN PUSKESMAS BERSERTIFIKASI INTERNATIONAL STANDARIZATION ORGANIZATION DENGAN NON INTERNATIONAL STANDARIZATION ORGANIZATION (Studi kasus : Puskesmas Pagu, Kecamatan Pagu dan Puskesmas Ngadiluwih, Kecamatan Ngadiluwih, Kabupat - TYAS, KUSUMANING (CITIZEN CHARTER, 2014)
ABSTRACT PHC (public health center) is a Unit of Technical Implementation District Health Office / City responsible arrangements for health development in the working area. As providers of health development, health centers are responsible for organizing the efforts of individual health and public health, which in terms of the National Health System, is a first-rate health care. The quality of health care affect the successful achievement of the health centers. In providing public services, the quality of service has become the main requirement for health centers. the functions of Public service related to the government's role, as a catalyst in fulfilling the public interest. Management system at Pagu's Public Health Center has been based on the quality management system ISO 9001: 2008.Therefore Pagu's Public Health Center directs the policies and processes within an organization shall be established, documented, implemented, measured and monitored, and further enhanced on an ongoing basis. While at the Ngaduluwih public health center has not been ISO certified, it still on the Service Excellence standards. Service Excellence is a management system that prioritizes on service excellence or the best service. Â Keywords: International Standardization organization, Excellent Service, Public Health Center.